Dampak Kebijakan Sekolah terhadap Pencegahan Anemia pada Siswa dan Tingkat Pengetahuan Remaja Putri Kelas X Tentang Anemia: SMK Negeri 9 Kota Padang - Waldatul Hamidah; Riska Pitriyani; Febrina Febrina (PPNI UNIMMAN, 2025)
Based on Indonesia's 2021 health profile, the coverage of iron supplementation (IBT) for adolescent girls in Indonesia, North Maluku ranks lowest among all provinces in Indonesia, at 2.1%, and West Sumatra province, at 11.5%, ranks 29th out of 34 provinces. The province with the highest percentage of iron supplementation coverage for adolescent girls (Ministry of Health, 2021). Anemia is a common health problem among adolescent girls. Many adolescent girls still face the dangers of anemia in Padang City. There is a risk of anemia in 193 adolescent girls, according to the Padang City Health Office's screening of grade X female high school, vocational high school, and Islamic high school students in 2021. The Padang Community Health Center's work area has the highest risk of anemia in adolescent girls, namely 96 people and a percentage of 21.91%. Screening conducted at the Padang Community Health Center workplace in 2021 found that SMKN 9 Padang had the highest risk of anemia in adolescent girls with 25 confirmed cases and a percentage of 26.31%. The purpose of this study was to determine the Overview of the Level of Knowledge of Grade X Female Adolescents About Anemia at SMK N 9 Padang City in 2025.This type of research is